2021
DOI: 10.1038/s41467-021-25404-x
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor recognition of hybrid insulin peptides bound to HLA-DQ8

Abstract: HLA-DQ8, a genetic risk factor in type I diabetes (T1D), presents hybrid insulin peptides (HIPs) to autoreactive CD4+ T cells. The abundance of spliced peptides binding to HLA-DQ8 and how they are subsequently recognised by the autoreactive T cell repertoire is unknown. Here we report, the HIP (GQVELGGGNAVEVLK), derived from splicing of insulin and islet amyloid polypeptides, generates a preferred peptide-binding motif for HLA-DQ8. HLA-DQ8-HIP tetramer+ T cells from the peripheral blood of a T1D patient are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…199 There is evidence that neoantigens involving the linkage of existing individual peptides can activate CD4 + T cells in type 1 diabetes (T1D), indicating that proteomic variants processes may generate MHC-II-associated neoantigens. 200 Several studies have reported that the spliced peptides produced by the proteasome are able to activate CD8 + T cells. 198,201,202 Splicetope-specific CD8 + T cells from TILs isolated from human AML patients inhibited the growth of their corresponding tumor cells in severe combined immunodeficient (SCID) mice model.…”
Section: Transcriptomic Variantsmentioning
confidence: 99%
“…199 There is evidence that neoantigens involving the linkage of existing individual peptides can activate CD4 + T cells in type 1 diabetes (T1D), indicating that proteomic variants processes may generate MHC-II-associated neoantigens. 200 Several studies have reported that the spliced peptides produced by the proteasome are able to activate CD8 + T cells. 198,201,202 Splicetope-specific CD8 + T cells from TILs isolated from human AML patients inhibited the growth of their corresponding tumor cells in severe combined immunodeficient (SCID) mice model.…”
Section: Transcriptomic Variantsmentioning
confidence: 99%
“…It can also respond to C-peptide which comprises half of the HIP. It responds moderately to full-length C-peptide (PI 33-63 ), but weakly to an 18mer fragment of C-peptide (PI 38-54 ) [ 36 ]. This allowed us to validate our system with a set of peptides known to vary in their capacity to stimulate this clone.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the scarce polar contacts seen in the three reported human TCR : HIP/DQ8 pairs are mediated by backbone oxygen and nitrogen atoms. Remarkably, however, the peptides bound to HLA-DQ8 molecules in the B-lymphoblastoid 9033 cell line were found to be highly enriched for presence of acidic residues at positions P5, P7 and P8 ( 37 ). This observation suggests that recognition of human HIPs carrying acidic residues at these positions by DQ8-restricted TCRs might be dictated by further molecular mechanisms that share common features with the 4.1-TCR : HIP39/I-A g7 signature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent structures of human TCRs bound to a HIP/HLA-DQ8 pMHCII complex ( 37 ) enable cross-species comparison for MHCII-presentation of HIPs. Despite the natural divergence in both the TCR repertoire and MHCII sequences, HIP presentation and recognition in the human and murine contexts follow a classical TCR:pMHCII binding pattern.…”
Section: Discussionmentioning
confidence: 99%